Flexitime : practices and experiences of selected Philippine-based organizations and a proposed model. - De Guzman, Marilou I. (Animo Repository, 1998)
The study, Flextime: Practices and Experiences of Selected Philippine-based Organizations and a Proposed Model, describes the Flextime Program of five Philippine-based organizations namely, Levi Strauss (Phil.) Inc., Philips (Electronics and Lighting), Nestle Philippines, Inc., Edward Keller Philippines, Inc., and Philamlife Insurance.This study is undertaken as a response to a lack of information about Flextime Program in the Philippines. It was viewed that with more empirically-based data from these Philippine-based organizations, that are practicing Flextime, quality of life will be better for working Filipinos. To be able to answer the questions raised, the researcher selected 50 participants from the five organizations -- 15 Supervisors and 35 Non-Supervisory. The Flextime Program Coordinator of the participating organizations chose the participants through random sampling technique. The demographic survey questionnaire has seven categories namely: sex, age, marital status, position in the organization, employment period, Flextime practice period, and Flexband morning attendance. On the other hand, the Interview Guides covered the questions of the Statements of the Problem of this study using open-ended questions for the Flextime Coordinator, Supervisors, and Non-Supervisors. Interviews were conducted individually from 15 to 30 minutes. Confidentialy of the participants' answers was assured to allow freedom of self-expression. Each interview session was recorded through a recording machine for accuracy of response.This study used descriptive method of studying how the participating organizations view their own Flextime Program based on the objective of this study. Data obtained from the interview were content analyzed, coded, and tabulated.